Politicizing Islam in Austria: the far-right impact in the twenty-first century - Hafez, Farid (Rutgers University Press, 2024)
"Among its Continental peers, Austria has stood out for its longstanding state recognition of the Muslim community as early as 1912. A shift has occurred more recently, however, as populist far-right voices within the Austrian government have redirected public discourse and put into question Islam's previously accepted autonomous status within the country. Politicizing Islam in Austria examines this anti-Muslim swerve in Austrian politics through a comprehensive analysis of government policies and regulations, as well as party and public discourses. In their innovative study, Hafez and Heinisch show how the far-right Austrian Freedom Party (FPÖ) adapted anti-Muslim discourse to their political purposes and how that discourse was then appropriated by the conservative center-right Austrian People's Party (ÖVP). This reconfiguration of the political landscape prepared the way for a right-wing coalition government between conservatives and far-right actors that would subsequently institutionalize anti-Muslim political demands and change the shape of the civic conditions and public perceptions of Islam and the Muslim community in the republic"--